Making time for life: A whole-of-industry initiative to reducing work hours and promoting health and gender inclusion in project-based construction work - Helen Lingard; Michelle Turner (Project Leadership and Society, 2022)
A cross section of participants representing a ‘vertical slice’ of the construction industry workforce were interviewed to: (i) understand the way that long hours are experienced by project-based workers and the factors contributing to the long hours culture, and (ii) explore the factors motivating a ‘whole of industry’ cultural reform initiative focused on reducing work hours in the Australian construction industry. Deeply entrenched systems of work within the construction industry, including competitive tendering processes and the imposition of financial penalties for time overruns, contribute to long work hours that are detrimental to workers' health and wellbeing. Moreover, construction companies develop project programs on the basis of assumptions that projects will run smoothly in all respects. Risks associated with program ‘slippage’ are passed down the supply chain to subcontractors. The problem of long work hours in construction project work means that a single organisation (whether client or constructor) cannot adequately address the issue. This has led to public sector client organizations and private sector construction organizations to engage in a unique collaborative initiative to reduce work hours and, in doing so, enable health, wellbeing and gender diversity in the Australian construction industry.